The Kurdish Resurrection Society (1942-1945) - Yazdani, Sohrab; Sajjadi, Amir (Journal of History Culture and Art Research, 2017)
The Kurdish Resurrection Society (known as Komeley Jiyanewey Kurd) was the first political society that was founded after August and September 1941 and following the Anglo-Soviet Invasion of Iran. This society arose from traditional and modern strata of urban Kurdish petty bourgeois in Mahabad. The present study aims at discussing the following questions applying a descriptive-analytical approach and using the historical resources and studies: 1. What is the role of the new social and historical structure of the Iranian Kurdistan in forming the Kurdish Resurrection Society? 2. How did the nationalism discourses of the modern absolutist Pahlavi state result in evolving the ideology of Kurdish Resurrection Society (KRS)? The evolution of KRS among the traditional and modern strata was the result of the changes and developments occurred in the structure of social forces in Iranian Kurdistan. These changes took place in the aftermath of modernization-related plans of the modern absolutist Pahlavi state in renewing the social structure and cultural assimilation of this era. This policy provoked a new form of collectivism based upon linguistic and ethnic minorities. In other words, while weakening and isolating the forces of the previous order, modernization paved the social and political ways needed for the emergence of new urban Kurdish forces. The Kurdish leaders and elites, affected by the nationalistic discourse of the modern absolutist Pahlavi state, attempted to provide a new definition of their ethnic identity. Thus, the nationalism discourse of the modern absolutist state led to the emergence of a particularistic nationalism discourse of KRS among the Kurds.